2008
DOI: 10.3748/wjg.14.7353
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol attenuates sepsis-induced gastrointestinal dysmotility in rats by modulating inflammatory mediators

Abstract: AIM:To investigate the protective effects of magnolol on sepsis-induced inflammation and intestinal dysmotility. METHODS: Sepsis was induced by a single intraperitoneal injection of lipopolysaccharide (LPS). Male Wistar ratswere randomly assigned to one of three treatment groups: magnolol prior to LPS injection (LPS/Mag group); vehicle prior to LPS injection (LPS/Veh group); vehicle prior to injection of saline (Control/Veh). Intestinal transit and circular muscle mechanical activity were assessed 12 h after L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 38 publications
4
35
1
Order By: Relevance
“…Magnolol, the major biphenyl compound ingredient of gardenia herbs, has emerged as a novel multifunctional tissue-protective agent with anti-edematous and anti-inflammatory effects (Yang et al, 2008). The pro-inflammatory cytokines play an important role in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Magnolol, the major biphenyl compound ingredient of gardenia herbs, has emerged as a novel multifunctional tissue-protective agent with anti-edematous and anti-inflammatory effects (Yang et al, 2008). The pro-inflammatory cytokines play an important role in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Yunhe et al (2012) demonstrated that magnolol attenuates the severity of lipopolysaccharide-induced lung injury and down-regulates the levels of TNF-α, IL-1β and IL-6 in mice. Yang et al (2008) reported that magnolol reduces gastrointestinal dysmotility in lipopolysaccharide-induced septic rats. In that study, the TNF-α mRNA expression in the small intestine was significantly reduced after magnolol treatment, while IL-10 mRNA expression was significantly increased in the ileum of magnolol-treated septic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies also demonstrated that magnolol has a board spectrum of anti-inflammatory effect. Magnolol was found to suppress the expression of the inducible nitric oxide synthase (iNOS) in macrophages (Matsuda et al, 2001), to inhibit inflammatory cytokines production in THP-1 cells and to attenuate septic shock in rats induced by surgical and endotoxin (Tsai et al, 2010;Yang, Zhang, Sun, Wang, & Ren, 2008). In addition, a recent study also showed that treatment with magnolol strongly inhibited TPA-induced skin inflammation and againsts DMBA/TPA-induced skin tumorigenesis in mice (Kuo et al, 2010).…”
Section: Introductionmentioning
confidence: 94%